Organism and environment in Auguste Comte. (July 2021) - McVeigh, Ryan
This article focuses on Auguste Comte's understanding of the organism–environment relationship. It makes three key claims therein: (a) Comte's metaphysical position privileged materiality and relativized the intellect along two dimensions: one related to the biological organism, one related to the social environment; (b) this twofold materiality confounds attempts to reduce cognition to either nature or nurture, so Comte's position has interesting parallels to the field of 'epigenetics', which sees the social environment as a causative factor in biology; and (c) although Comte ultimately diverged from the 'postgenomic' view in crucial ways, he remains a forerunner of the trend towards viewing the social and biological as entangled. Tending to these dimensions challenges the view that Comte is notable from a classical standpoint but ignorable from a contemporary one. It consequently invites renewed attention to his theoretical system.